Fleas (Siphonaptera) of Small Mammals in Steppe of Don Region - B. K. Kotti; V. V. Stakheev; A. V. Zabashta (Наука. Инновации. Технологии, 2022)
Introduction. The territory located within the Steppe Don (Rostov region) is relatively well studied in relation to the flea fauna of small mammals, with the exception of its northern part. The bulk of research was conducted in the first half - mid-twentieth century. However, during the time that separates this period and the present day, the natural environment and the animal population of the region have undergone a transformation, and there have been noticeable changes in the taxonomy of both fleas and their mammalian hosts. Our work covered a signiicant part of small mammal species and the territory of the Steppe Don region; it allowed us to clarify information about the specificity of parasite-host relationships and distribution for a number of species. Materials and methods of the research. Small mammals were caught in semi-desert, steppe, meadow and forest biotopes in all seasons 1997-1998, 2006-2008, and 2014-2020. The work covered a signiicant part of the species of small mammals and the territory of the Steppe Don region. The results of the study and their discussion. The data on 29 species of leas known from small rodents, insectivores and their nests are presented. In terms of distribution, the species form three groups: inhabiting the entire territory of the Steppe Don region; inhabitants of the wormwood-fescue steppe subzone; species limited to the subzone of the forb-cereal steppe. Conclusions. The study made it possible to clarify for a number of flea species information on the speciicity of host-parasite connections and distribution within the Steppe Don region. The lea list of small mammals includes 29 species. Megabothris turbidus, Ceratophyllus sciurorum, Ctenophthalmus proximus, Palaeopsylla soricis and Hystrichopsylla talpae were found here for the irst time.